COMMON FIXED POINTS IN b-DISLOCATED METRIC SPACES USING (E.A) PROPERTY - Zoto, Kastriot; Vardhami, Ilir; Dine, Jani; Isufati, Arben (Matematichki Bilten, 2016)
In this paper, we prove coincidence and common fixed point results for one a pair of mappings that satisfy the (E.A) property and its generalized variants in the setup of b-dislocated metric spaces. Our results generalize and extend some existing results in the literature.